Using cognitive interviewing to improve the Women’s Empowerment in Agriculture Index survey instruments: Evidence from Bangladesh and Uganda - Malapit, Hazel J.; Sproule, Kathryn; Kovarik, Chiara (International Food Policy Research Institute, 2016)
This paper describes the cognitive interviews undertaken in Bangladesh and Uganda in 2014 as part of the second round of pilots intended to refine the original version of the Women’s Empowerment in Agricultural Index (WEAI). The WEAI is a survey-based tool that assesses gendered empowerment in agriculture. Baseline data were collected in 19 countries following the WEAI’s launch in 2012, but implementers reported a number of problems, such as confusion among both respondents and enumerators regarding the meaning of abstract concepts in the autonomy sub-module and difficulties recalling the sequence and duration of activities in the time-use sub-module. In our cognitive interviews, we asked detailed follow-up questions such as, “Did you think this question was difficult, and if so, why?” and “Can you explain this term to me in your own words?” The results revealed potential problems with the survey questions and informed the revision of the WEAI, now called the Abbreviated WEAI (or A-WEAI), which has less potential for response errors.